The Impact of Zakat Literacy, Trust, and the Accessibility of Digital Payments on Generation Z and Y's Intention to Pay Zakat to Central Zakat Fund, the State Bank of Pakistan - Zahid Hussain; Raja Sultan; Asadullah Asadullah; Muhammad Arif; Aftab Ali (International Journal of Zakat, 2022)
Even though 96% of Pakistan's population is Muslim, the enormous capacity for zakat management in Pakistan has sadly not been utilised. Several Muslim groups in Pakistan prefer to contribute their zakat immediately toward the Central Zakat Fund instead of officially to the government. This behaviour has turned into a major issue that needs to be investigated and fixed. In this research, several variables are examined, including zakat literacy, trust, and the accessibility of digital payments, which have been linked to people's intentions toward zakat collection and zakat management organizations are examined. A sample of 100 young Muslims, specifically members of generation Z as well as the millennials, participated in this study in Sindh. The analysis method used was multi-regression analysis. The findings indicated that the Zakat literacy variable had a limited impact on Generation Z and Millennials' intentions to make zakat payments to zakat management organizations. While Generation Z and Millennials' intentions to contribute zakat to zakat management organizations are somewhat influenced by the factors of trust and accessibility of electronic payments. These three different research factors have an impact on Millennials and Generation Z's intentions to contribute zakat to zakat management organizations concurrently. Overall, 64.8% of the variance in the Y variable could be explained by three main research variables X.